Penerapan Tri-N Pada Buku Siswa Bahasa Indonesia VIII Dalam Upaya Meningkatkan Keterampilan Berbahasa - Siti Rochmiyati; Die Bhakti Wardoyo Putro (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to describe the application of Tri-N in Indonesian Literature textbooks for SMP VII Class Curriculum 2013 in an effort to improve writing and speaking skills. This research is a descriptive qualitative research with a scientific approach. The results of class VIII research show that the application of the niteni, nirokke, and add processes to each process in literary texts as an effort to improve students' writing and speaking skills so as to improve more creative and productive cognition. The application of niteni in an effort to improve writing skills is found in words or clauses, such as note down the rules, while speaking skills, such as present and explain. The application of nirokke in writing skills, such as note-taking and serving, while speaking skills, such as staging and reciting. The application of increment in writing skills, such as making sentences and making reports, while speaking skills, such as speaking and reporting.